2017
DOI: 10.1155/2017/6586438
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Wave Velocity-Permeability Model for Granite Subjected to Different Temperature Processing

Abstract: Understanding the change of permeability of rocks before and after heating is of great significance for exploitation of hydrocarbon resources and disposal of nuclear waste. The rock permeability under high temperature cannot be measured with most of the existing methods. In this paper, quality, wave velocity, and permeability of granite specimen from Maluanshan tunnel are measured after high temperature processing. Quality and wave velocity of granite decrease and permeability of granite increases with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Skalny [15,16] first proposed to investigate the permeability characteristics of the ITZ by comparing the permeability test results of pure rock, cement-based and cement slurry-rock. Subsequently, many scholars have obtained the permeability of the ITZ by this method and proved that the permeability of the ITZ is far greater than mortar [17,18]. However, some scholars have assumed that although the permeability of the ITZ is large, it is not necessarily the permeability channel of the whole structure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Skalny [15,16] first proposed to investigate the permeability characteristics of the ITZ by comparing the permeability test results of pure rock, cement-based and cement slurry-rock. Subsequently, many scholars have obtained the permeability of the ITZ by this method and proved that the permeability of the ITZ is far greater than mortar [17,18]. However, some scholars have assumed that although the permeability of the ITZ is large, it is not necessarily the permeability channel of the whole structure [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, confining pressure also affects the permeability properties of the rocks. In addition, the relationship between the permeability and the porosity of rock has also been studied [22,[26][27][28][29][30]. Chaki et al [22] studied the porosity and permeability evolutions of thermal damage granite, and results showed that the permeability measurement can better characterize the porosity and connected porosity of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Chaki et al [22] studied the porosity and permeability evolutions of thermal damage granite, and results showed that the permeability measurement can better characterize the porosity and connected porosity of the specimen. Jiang et al [26] established a new wave velocity-permeability model for granite subjected to different temperatures according to the modified wave velocity-porosity formula and Kozeny-Carman formula. Jia et al [27] and Zheng et al [28] studied the effective stressdependent permeability and porosity of low-permeability rock, and results showed that a power-law form can be used to describe the correlation of permeability and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, ultrasonic wave velocity measurements can be used to determine the anisotropy and the microcrack evolution of rocks during loading [18][19][20][21]. Furthermore, the permeability and the porosity of rocks also can be determined based on the connection between mesostructures of rock and ultrasonic wave velocity [22][23][24]. However, all the predictions by using the wave velocity measurements are statistical equations and have a certain error.…”
Section: Introductionmentioning
confidence: 99%